PENGARUH TEMPERATUR TERHADAP DAYA LENTING BERBAGAI MACAM KAWAT BUSUR NIKEL TITANIUM (Eksperimental Laboratoris) - , Rina Setiowati; , drg. Hj. Sri Suparwitri, SU., Sp.Ort. (K). ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Archwire is one of important component on orthodontic appliance. The metal materials of archwire are progressed quickly, especial a Nickel Titanium archwire wich is used on initial treatment orthodontic. Many kinds and types of archwires are available at present, the orthodontists should have a good knowledge about its variations and characteristics. The aim of this study was to know the influence at temperature differences towards springback power of Nickel Titanium archwire. This study was carried out on China, Lowland, GNH, IMD, and Orthomerica Nickel Titanium archwires. Each Nickel Titanium to consist of 15 archwire with a length of 12,5 mm, diameter of 0,016 inches, divided into 3 groups and every group consist of 5 archwires. Each groups submerged in artificial saliva on 10 0 C, 37 0 C and 60 0 C with normal pH, then the springback power were measured with deflection gauge. The result of this study showed that there were very significant differences of springback power value which is equivalent to the required load on each archwire of Nickel Titanium with temperatur change. The Nickel Titanium archwire IMD, Orthomerica, and China rangked first, second and third at temperatures 10 0 C, 37 0 C and 60 0 C, therefore all three Nickel Titanium archwire IMD, Orthomerica and China require large load to deflection of 1 mm compared to both Nickel Titanium archwire Lowland and GNH and thus have a high springback. The conclusion that were differences in the effect of temperature change influence against springback power China, Lowland, IMD, GNH and Orthomerica Nickel Titanium archwire. The springback power would be high when the temperature is less and more than 370C.